Model Lapis Tipis Pengeringan Menggunakan Metode Pengering Rak - UNDIP-Semarang), Suryanto (Jurusan Teknik Mesin, POLINES-Semarang), Kristinah Haryani, Suherman (Jur (Teknis, 2015)
Ginger (Zingiber officinale Rosc.) is one of the agricultural commodities such as spice plants that have high economic value. Drying ginger is one way to improve the product quality with a lower moisture content materials. This research was carried out by using a tray dryer with drying temperature are 40oC, 50oC and 60oC. The type of the dried ginger are red ginger, small ginger and big ginger. Sample is peeled before and cut to produce a thickness of sample 1,5cm, 1 cm and 0,5cm. After drying for 4hours, that known the drying rate increases with an increase in drying temperature. Drying rateis also influenced by the surface area of the sample ginger. The best drying rate obtained from ginger samples with a thickness of 0,5 cm. Three thin-layer drying models are used to compare the rate of moisture rate modeling with moisture rate experiments. Pag emodel is a model of a thin layer which can prove that the moisture rate modelling and moisture rate experiment has the best statistical correlation. Drying will cause a change in color, texture and shape of the sample. Ginger drying using tray dryer, the sample sizes hould be minimize and dried at 60oC.Keywords: Ginger Rhizome, Drying, Tray Dryer, Thin Layer Drying.